Response of Several Types of Manure And Dosages on Cabbage (Brassica Oleracea L.) Growth and Yield (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
This research was conducted in Tiga Runggu, Simalungun Regency, Indonesia. This research was conducted using a factorial randomized block design consisting of two factors, i.e. application of manure types consisting of 3 treatments, namely J1: chicken manure, J2: cow manure and J3: buffalo manure. The second factor consisted of three treatments, namely: D1: 75g/plant, D2: 100g/plant, and D3: 125g/plant. The parameters observed in this study were: (a) rate of crop formation, (b) gross crop weight per sample plant, (c) net crop weight per sample plant, (d) gross crop weight per plot, and (e) net crop weight per plot. The results of the study showed that the type of manure treatment had a significant effect on the rate of crop formation, gross crop weight per sample plant, net crop weight per sample plant, gross crop weight per plot and net crop weight per plot.